INSIGHT: Improving Numeracy Skills on Integers through e-Games and Hands-on Technology - Renante E. De La Torre Jr; Hazel G. Andrada; Jhan Joy C. Catador; Christalyn Tan; Mary Jane Pantonial; Dannaliza Panaga (Research Synergy Foundation, 2026)
Due to the school lockdown during the COVID-19 pandemic, students' numeracy skills declined. This was evident in the ERUNT conducted at Sagay National High School, which showed that among students in Grades 7 to 11, 40.77% are non-numerate in performing operations involving integers. Hence, the researchers conducted quasi-experimental classroom-based action research to propose a solution to this problem. The study was participated in by thirty-six (36) Grade 9 – Aquamarine students enrolled for the school year 2022 – 2023. The intervention used an offline e-game (Integer Saga) via immediate, hands-on technology (smartphones), which students used for fifteen (15) days in a controlled gameplay setting. Pre- and post-numeracy tests were conducted to determine the effectiveness of the intervention. The statistical tools used in the study are frequency and percentage, mean and standard deviation, paired t-test, and Pearson r. The results revealed an increase in the participants' numeracy in performing operations on integers after the intervention. A significant difference between the pre- and post-test results was observed, indicating that the intervention effectively increased participants' numeracy skills. Furthermore, the time spent using the application and the participants' post-test results were positively correlated. These results imply that the proposed intervention is effective in increasing students’ numeracy skills, specifically in algebra. Therefore, it is recommended that this intervention be used to improve students' numeracy skills, specifically to develop mastery of performing operations on integers.